Background Contamination of the Project Hephaistos Dyson Spheres Candidates - Ren, T; Garrett, MA; Siemion, APV (American Astronomical Society, 2024)
Project Hephaistos recently identified seven M-dwarfs as possible Dyson Spheres (DS) candidates. We have cross-matched three of these candidates (A, B and G) with radio sources detected in various all-sky surveys. The radio sources are offset from the Gaia stellar positions by ∼4.9, ∼0.4 and ∼5.″0 for candidates A, B, and G respectively. We propose that Dust obscured galaxies (DOGs) lying close to the line-of-sight of these M-dwarf stars significantly contribute to the measured WISE mid-IR flux densities in the WISE W3 and W4 wave bands. These three stars have therefore been misidentified as DS candidates. We also note that with an areal sky density of 9 × 10−6 per square arcsecond, Hot DOGs can probably account for the contamination of all 7 DS candidates drawn from an original sample of 5 million stars.